Alternative pathways for sustainable energy development and implications for water and food security in the Philippines - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The Philippines currently relies largely on fossil-fuel based power generation (about 77 percent) and is expected to increase power generation from coal-based (fossil) plants to meet future energy demand, which would negatively affect environmental outcomes. Primary energy supply is expected to double between 2011 and 2030. The renewable energy potential is relatively high in the Philippines and could contribute to supply modern reliable energy services and improve energy security. The government’s energy reform agenda highlights the importance of access to more reliable energy using indigenous energy resources while minimizing imported fossil-fuel use in an optimal and cost-effective way. The feasibility of this type of diversification from fossil-fuel to renewable energy based power generation can be assessed by applying energy optimization models, such as MARKAL1/TIMES2. Application of a bottom-up energy optimization model can provide important insights into the implications of prospective conversion technologies that can be pursued by the Philippine government in a cost-efficient and effective way to ensure energy security and develop a low-carbon society.